Cost Structure and Profit Obtained in Instant Red Ginger Drink Business - antriadisti, Shinta T; Humaidi, Edy; Sudiyo, Sudiyo; Ulfah, Maria (ABEC Indonesia, 2024)
Red ginger is one of the biopharmaceutical plants that became a favorite when the Covid19 pandemic brokeout. Red ginger can be used as a base for drinks that can increase the body's immunity. Processing red ginger into instantginger drink can provide more economic value to the red ginger commodity itself. With a higher economic value, it willbe possible to increase the profits obtained, so that in the end it will increase farmers' interest in producing the red gingercommodity. In order to further increase profits from the instant red ginger drink business, it is necessary to look at theanalysis of the cost structure and profits obtained as well as the efficiency of the business. The aims of this research are toanalyze the cost structure and profit as well as the efficiency of the instant red ginger drink processing business. Theresearch method used is the case study method. This research was carried out at the Zala Red Ginger UMKM in SouthLampung Regency. The location was chosen deliberately with the consideration that the Zala Red Ginger UMKM is oneof the red ginger agro-industry in South Lampung Regency. This research was carried out from April to September 2024.The results of this research are that the largest proportion in making instant red ginger drinks for UMKM Red Ginger is theraw material cost of red ginger, which is 66,99% and the second largest proportion is packaging costs, which is 13,40% ofthe total costs incurred. The profit obtained by the Zala Red Ginger UMKM instant ginger drink processing business wasIDR 5,035,750.00. The R/C or efficiency of the Zala Red Ginger UMKM instant ginger drink processing business is 1.67